Adsorption of Zn(ii) on amination@wood-aerogel and high-value reuse to ZnO/ZnS as an efficient photocatalyst. Issue 36 (23rd August 2022) - Zhang, Wanqi; Li, Lili; Zhang, Xiaotao; Liu, Hui; An, Yuhong; Zhong, Yuan; Hu, Zichu; Shan, Xiaofei; Wu, Jing; White, Marshall; Chen, Zhangjing; Wang, Ximing
Abstract : A top-down approach to generate Amination@Wood-Aerogel (AWA) with high adsorption capacity for Zn(ii ). Then in situ construction of ZnO/ZnS heterojunction in hazardous solid waste Zn(ii )-loaded-AWA and followed by photocatalytic degradation of Congo red. Abstract : What should be done after an adsorbent has adsorbed heavy metals? Most previous studies on adsorption materials only focused on the preparation method and adsorption capacity and seldom considered the potential pollution of hazardous waste adsorbents. In this study, we not only designed an Amination@Wood-Aerogel (AWA) bulk adsorbent with easy recovery and high adsorption capacity for Zn(ii ) (400 mg L −1, 297.03 mg g −1 ) but also for the first time proposed a novel high-value reuse strategy for the in situ conversion of Zn(ii ) adsorbed onto AWA to ZnO/ZnS n-type heterojunction photocatalyst (ZnO/ZnS@AWA) via in situ chemical deposition, which will be further used for the photocatalytic degradation of Congo red. The adsorption sites (–OH, –COOH, –NH2 ) on the AWA surface ensure that ZnO/ZnS could cover the AWA surface evenly with strong interfacial bonding strength. ZnO/ZnS@AWA successfully photocatalytically degraded Congo red (40 mg L −1, 98.84%) through the synergistic degradation mechanism of adsorption and photocatalysis. This work proposes a new protocol for wood-based bulk adsorbents and provides a high-value reuse strategy for solving the potential pollution of hazardous waste adsorbents. It is indisputable that we point out a new direction to design adsorbents with high adsorption capacity and high-value reuse.